1997
DOI: 10.1042/bj3220455
|View full text |Cite
|
Sign up to set email alerts
|

A potent and highly selective peptide substrate for protein kinase C assay

Abstract: Protein kinases exhibit substrate specificities that are often primarily determined by the amino acids around the phosphorylation sites. Peptides corresponding to protein kinase C phosphorylation sites in several different proteins were synthesized on SPOTs membrane which has recently been found to be applicable for studies of protein kinase specificity. After phosphorylation with protein kinase C, we chose the best phosphorylated peptides for the investigation of the importance of amino acids immediately adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…The SPOT method has been used successfully to identify substrate sequence motifs for a number of protein kinases (27,28). In this study, we have expanded the practical utility of the SPOT method and demonstrated that peptide libraries specifically designed to screen for binding combinations lead to peptides that are potent inhibitors of cGPK.…”
Section: Discussionmentioning
confidence: 99%
“…The SPOT method has been used successfully to identify substrate sequence motifs for a number of protein kinases (27,28). In this study, we have expanded the practical utility of the SPOT method and demonstrated that peptide libraries specifically designed to screen for binding combinations lead to peptides that are potent inhibitors of cGPK.…”
Section: Discussionmentioning
confidence: 99%
“…3A). Inasmuch as both serine and threonine may serve as phosphorylation residues within the theoretical mutated PKC consensus sequence, these results suggest that phosphorylation may perhaps be an important regulator of ORNT1 function (13). Future studies will explore this intriguing observation.…”
mentioning
confidence: 96%
“…Furthermore, Thr 32 has been conserved throughout evolution thus suggesting an important role in ORNT1 protein function. Interestingly, this amino acid change, T32R, abolishes a theoretical protein kinase C (PKC) phosphorylation site (Ser/Thr-Xaa-Arg/Lys) (13).…”
Section: Missense Mutation (T32r) In Hhh Syndromementioning
confidence: 99%
“…The phosphorylatable serine residue of sucrose synthase 2 is surrounded by the peptide sequence RVLSRLHS 15 VRER, with several positively charged amino acids before and after the Ser15 residue. This means that the substrate specificity of the relevant plant protein kinase(s) should follow similar principles to that of a large group of mammalian protein kinases, showing selectivity for positively charged amino acids [8].…”
Section: Camentioning
confidence: 99%
“…The phosphorylation reactions were carried out at 30 8C essentially as described in [15]. The specific radioactivity of [g-32 P]ATP was 50±150 c.p.m.´pmol 21 .…”
Section: Phosphorylation Of Spots Peptidesmentioning
confidence: 99%